2007
DOI: 10.1158/1055-9965.epi-06-1038
|View full text |Cite
|
Sign up to set email alerts
|

Number of Nevi and Early-Life Ambient UV Exposure Are Associated with BRAF-Mutant Melanoma

Abstract: Malignant melanomas often contain BRAF or NRAS mutations, but the relationship of these mutations to ambient UV exposure in combination with phenotypic characteristics is unknown. In a population-based case series from North Carolina, 214 first primary invasive melanoma patients in the year 2000 were interviewed regarding their risk factors. Ambient solar UV exposures were estimated using residential histories and a satellite-based model. Cases were grouped on the basis of BRAF and NRAS somatic mutations, dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
174
1
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 49 publications
14
174
1
9
Order By: Relevance
“…Age-specific incidence patterns display early-and late-onset peak frequencies for trunk and face/ear melanomas, respectively [130,131], consistent with hypotheses that melanoma arises from more than one causal pathway and contain distinct melanoma genotypes [241]. NRAS and BRAF mutations, mutually exclusive of each other, are found, respectively, in 10-30 and 25-60 % of primary melanomas [60,63,64,93,228]. Less frequently, melanomas contain KIT mutations, particularly mucosal melanoma or melanomas arising on acral or on sun-damaged sites [53].…”
Section: Somatic Genetic Factors: Tumor Subtypessupporting
confidence: 65%
See 3 more Smart Citations
“…Age-specific incidence patterns display early-and late-onset peak frequencies for trunk and face/ear melanomas, respectively [130,131], consistent with hypotheses that melanoma arises from more than one causal pathway and contain distinct melanoma genotypes [241]. NRAS and BRAF mutations, mutually exclusive of each other, are found, respectively, in 10-30 and 25-60 % of primary melanomas [60,63,64,93,228]. Less frequently, melanomas contain KIT mutations, particularly mucosal melanoma or melanomas arising on acral or on sun-damaged sites [53].…”
Section: Somatic Genetic Factors: Tumor Subtypessupporting
confidence: 65%
“…These findings are plausible as approximately 70 % of nevi contain BRAF mutations [194]. BRAF mutations were associated with the ability to tan but not with freckling or hair or eye color [93,228]. TERT promoter mutations in melanoma were not associated with hair, skin, or eye color or number of nevi [101].…”
Section: Clinical Characteristics Of Tumor Subtypesmentioning
confidence: 87%
See 2 more Smart Citations
“…The presence of both NRAS and BRAFV600E mutations in the same lesions is contrary to the current consensus that such mutations are almost always mutually exclusive in melanomas and other tumor types. [17][18][19] However, Pollock et al 20 observed concomitant NRAS and BRAFV600E mutations in 9% of nevi and suggested this might be because of different clonal nests of cells within these tumors carrying distinct mutations. In our case carrying both NRASQ61R and V600E mutations, immunohistochemistry with VE1 and N-Ras (Q61R) antibodies allowed direct visual confirmation of the BRAFV600E-and NRAS-mutated positive status in the same tumor cell population.…”
Section: Discussionmentioning
confidence: 99%